Effects of plant community composition and flowering phenology on honeybee foraging in Mediterranean sylvo‐pastoral systems. Issue 4 (7th January 2013) - Bagella, Simonetta; Satta, Alberto; Floris, Ignazio; Caria, Maria Carmela; Rossetti, Ivo; Podani, János; Acosta, Alicia
Abstract Questions Which are the most effective plant communities for honeybee foraging and honey production in Mediterranean sylvo‐pastoral systems? What is the relationship between flowering phenology and pollen occurring in honey sediments? Location Mediterranean sylvo‐pastoral system in Gallura, Sardinia, Italy. Methods Phytosociological and phenological surveys were performed in a circular area of 1.5 km radius with a small apiary placed in the centre. Polleniferous and nectariferous values of plant communities were assessed based on the cover and the polleniferous and nectariferous value of each constituting species. Honey production was quantified during the main flow (March–June) and subjected to melissopalynological analysis. Data were evaluated by ordination through principal components analysis and principal coordinates analysis. The latter utilized a new index, developed for calculating the phenological distances based on the individual distributions of flowering frequencies. Results Plant communities richest in species providing pollen and nectar were Rhamnus hedges. There was a close correlation between polleniferous and nectariferous values, suggesting that plant communities are important for honeybee foraging of both resources. The temporal flowering sequence ensured the supply of nectar and pollen throughout the spring season. Pollen foraged from 12 Trifolium species with different flowering phenology was the most abundant. Salix purpurea and Rhamnus alaternus were productive at the beginning of the season, followed by Lavandula stoechas, Echium plantagineum and E. italicum. Conclusions Plant communities vary in importance for honeybee foraging mainly due to differences in floristic composition and flowering phenology. Communities characterized by human presence (e.g. semi‐natural grasslands and hedges) are the most relevant. Some target species (e.g. Trifolium spp.) favoured by grazing livestock ensure foraging for honeybees throughout the season. Plant communities of wild areas, such as the garrigue vegetation, provide foraging for unifloral valuable honey (i.e. 'Lavandula' honey).